STUDI VIABILITAS ISOLAT BAKTERI ASAM LAKTAT YANG DIISOLASI DARI ASINAN REBUNG BAMBU TABAH TERHADAP pH RENDAH DAN GARAM EMPEDU - Wasis, Nurul Octavia; Semadi Antara, Nyoman; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): Maret, 2019)
Tabah bamboo shoot pickle is one of the fermented food which is the source of lactic acid bacteria.  Lactic acid bacteria (LAB) is beneficial to health because it has the ability as a probiotic. Lactic acid bacteria that have probiotic criteria should have resistance to low pH and bile salts. This study aims to determine isolates of lactic acid bacteria isolated from tabah bamboo shoot pickle resistant to low pH and bile salts (NaDC). Lactic acid bacteria were tested to low pH by using MRS broth that have different pH (pH 2, pH 3, pH 4 and pH 6.2 as a control) incubated at 37ºC for 3 hours. isolates were survive in low pH then continued in bile salt resistance test with 0.3% bile salt concentration for 15 minutes, 30 minutes, 45 minutes, 60 minutes and 24 hours. The results showed that three isolates out of 88 isolates had ability to grow in low pH and in medium supplemented by NaDC 0,3%. The isolates are AR 3057, AR 3101 and AR 6152 which can be used as candidat of  probiotic. Keywords : Tabah bamboo shoot pickle, lactic acid bacteria, probiotic, low pH, bile salt